2020
DOI: 10.2147/cmar.s273084
|View full text |Cite
|
Sign up to set email alerts
|

<p>Efficacy and Adverse Effects of Self-Expandable Metal Stent Placement for Malignant Duodenal Obstruction: The Papilla of Vater as a Landmark</p>

Abstract: Self-expandable metal stents are used for malignant duodenal obstruction. Outcomes between stents placed above and below the papilla of Vater differ, and no study has investigated these differences. We evaluated the efficacy and adverse events of stent placement in these two locations and reported our experience with self-expandable metal stent placement in patients. Patients and Methods: We retrospectively analyzed the data of patients with unresectable metastatic cancers (n = 101), who underwent successful d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
(31 reference statements)
2
7
0
Order By: Relevance
“…Despite these difficulties mentioned, Wu et al . disclosed an equal efficacy of stenting between the patients with duodenal obstruction levels above and below the major papilla, with no increased adverse events in the below papilla group [ 14 ]. However, the long-term outcomes following metallic stenting on different duodenal portions and predictors for prognosis were not analyzed in their study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these difficulties mentioned, Wu et al . disclosed an equal efficacy of stenting between the patients with duodenal obstruction levels above and below the major papilla, with no increased adverse events in the below papilla group [ 14 ]. However, the long-term outcomes following metallic stenting on different duodenal portions and predictors for prognosis were not analyzed in their study.…”
Section: Discussionmentioning
confidence: 99%
“…further compared the clinical outcomes between patients who received SEMS for the obstruction level above the major papilla (including papilla itself) and below the major papilla, with technical success rates of 100% and 93%, respectively. The clinical success rates were 100% in both the above-papilla and below-papilla groups [ 14 ]. Though these studies disclosed that palliative stenting in duodenal obstruction is clinically effective, factors that influence the prognosis in these patients remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Dormian et al [ 18 ] reported that SEMSs is technically successful in 97% of cases and clinically successful, measuredas the ability of a patient to tolerate oral intake, in 87%. However, SEMSs are associated inthe long term witha high risk of stent occlusion and migration;other complications reported are duodenal bleeding and perforation [ 19 ]. SEMSs should probably be considered the best option in patients with poor general condition and a theoretically short life expectancy;meanwhile, surgery still represents a first optionfor patients with a longer life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…According to the classification system, this case was a type II stenosis because of the involvement of the second part of the duodenum and papilla. In this case, anendoscopic procedure alonewould have beendifficult, so a biliary stenting through the mesh ofthe duodenal SEMS was used to resolve the double strictures using a procedure known as the rendezvous technique, an intervention thatcombines both endoscopic and percutaneous approaches [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Type III stenosis involves the third section of the duodenum, distal to, and without involvement of the papilla. We simplified the position of duodenal obstruction into two categories, namely the above-papilla type (comprising patients with duodenal obstruction from the bulb to the papilla of Vater itself) and the below-papilla type (comprising patients with duodenal obstruction below the papilla, including the lower part of the second section of the duodenum to the proximal jejunum) owing to different clinical backgrounds and technical challenges [23]. Logistic regression analysis determined that the events associated with duodenal obstruction below the papilla of Vater (type III in Mutignani's classification) were risk factors for DBR-related covered SEMS dysfunction.…”
Section: Discussionmentioning
confidence: 99%